# math

multiply

�ã7(�ã10-�ã6)

so would this be �ã70-�ã42

1. 👍
2. 👎
3. 👁

## Similar Questions

1. ### Math

A student is trying to solve the set of two equations given below: Equation A: x + z = 6 Equation B: 2x + 4z = 1 Which of the following is a possible step used in eliminating the z-term? Multiply equation B by 4. Multiply equation

2. ### Algebra

In an arithmetic sequence where a6=13 and a10=25, what is the explicit formula for the general term an?

3. ### Math

Let a1,a2,......a10 be an arithmetic sequence. If a1+a3+a5+a7+a9=17 and a2+a4+a6+a8+a10=15 then find a1.

4. ### Mathematics

Write a rule for the nth term of the sequence. Use your rule to find a70. –10, –8, –6, –4, –2, . . .

1. ### Math

Which inverse operations could you use to solve the equation m/5 - 8 = -6? Select two answers A. Add 8 to each side and then divide each side by 5. ***B. Add 8 to each side and then multiply each side by 5. C. Multiply each side

2. ### advanced math

suppose that a1, a2, a3, ..., ak forms an arithmetic sequence. If a5+a8+a11=10, a7+a10+a13=12, and ak=11, find k note: the numbers and the k after the a's are subscript but i don't know how to type that

3. ### Math

A polynomial function with rational coefficients has the following zeros. Find all additional zeros. 2, -2 + ã10

4. ### math

Brett has been studying a type of bacteria that doubles every month. Originally, there were 5 bacterial cells. He wants to know how many there will be after 42 months. Which equation should he use? a42 = 5(2)42 − 1 a42 =

1. ### MATH

HOW TO SOLVE THIS? ã8(ã10-1) PLEASE IT IS URGENT !!!!

2. ### Statistics 2

To calculate the mean for grouped data, which of the following steps must be completed? a. multiply the number of subjects within each category by the value of that category b. divide the results of the multiplication c. multiply

3. ### Math

Find r in a geometric sequence if A=2 and A10=1024

4. ### algebra II

Select the best possible first step to solving the system by first eliminating the y variable. x + 8y = –4 2x – 4y = –13 Multiply the first equation by 2. Multiply the second equation by 2. Multiply the first equation by